The Influence of speech skills on social interaction student STIAB JINARAKKHITA - Iin Avitasari; Candra Kusuma; Vike Aprilianin Marwintaria Saputri; Rapiadi; Rina Manggalani (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
This research aims to investigate the influence of self-concept on the quality of interpersonal communication of Jinarakkhita Buddhist Collage of Lampung students. Self-concept is an important factor in understanding how a person interacts with other people. The quality of interpersonal communication also has a key role in establishing healthy and productive relationships in various life contexts. This research uses a survey method by collecting data through questionnaires distributed to Jinarakkhita Buddhist Collage of Lampung students. The questionnaire measures students' self-concept and quality of interpersonal communication. The collected data is then analyzed using appropriate statistical techniques. The results of this research indicate that there is a significant influence between self-concept and the quality of interpersonal communication of Jinarakkhita Buddhist Collage of Lampung students. These results indicate that students who have a positive self-concept tend to have better interpersonal communication quality. This indicates the importance of developing self-concept in the context of higher education to improve the quality of social interaction and interpersonal communication. This research can be a basis for educational institutions to consider programs that can help students develop a more positive self-concept, so that they can become more effective individuals in communicating and establishing healthy interpersonal relationships in the campus environment and outside the campus.